An extension of the SEMAT kernel for representing teaching and learning practices about embedded systems (2016)
Demand for embedded systems has increased in recent years. This demand requires engineers with specialized skills and knowledge. For this, the higher education institutions are developing training strategies aimed primarily at lectures and laboratory practices. However, these strategies are insufficient for the development of technical and social skills required by engineers. In addition, currently there is a lack of a common framework to facilitate teaching-learning process and achievement of learning objectives. In this paper, the authors present a proposal for representation of teaching and learning practices about embedded systems, which have been oriented to track and encourage competency development. The proposal is based on the SEMAT kernel as universal framework for representing software engineering practices, defining an extension to such kernel. In addition, a methodology is proposed with a practical approach for creating theories related to computing, this methodology is used to define an extension of the SEMAT kernel for another discipline domain. In this paper, a first form of general representation of teaching and learning practices about embedded system is proposed. The proposal includes the minimum elements that should have any practice of teaching and learning about embedded systems, and the extension mechanisms to represent specific elements.